Concepto y Régimen Jurídico del Servicio Público en el Ordenamiento Público Peruano - Huapaya Tapia, Ramón (Pontificia Universidad Católica del Perú, 2015)
The author proposes a review of the different experiences relating to public services of economic content, both nationally and internationally, and then he analyze its concept and legal framework in national law. to this end, he reviews therecent literature on the subject, the constitutional basis and the relevant case law in order to offer his concept of Guarantor state , linked to the role and concept of public service in the peruvian legal system.

El autor propone una revisión de las diferentes experiencias relativas a los servicios públicos de contenido económico, tanto a nivel nacional como internacional, paraluego analizar su concepto y régimen jurídico en el ordenamiento nacional. Para ello, pasa revista a la literatura más reciente sobre la materia, las bases constitucionales y la jurisprudencia más relevante, para así ofrecer su concepto de estado/Administración garante, vinculado al rol y concepto del servicio público en elordenamiento jurídico peruano.
Concept and Legal Regime of Public Service in the Peruvian Public Law
Keywords: Public Service; Subsidiarity Principle; Economic Administrative Law; Economic Regulation; Regulatory State; State Guarantor; Servicio Público; Principio de Subsidiariedad; Derecho Administrativo Económico; Regulación Económica; Estado Regulador; Estado Garante; https://purl.org/pe-repo/ocde/ford#5.05.00